Estudo óptico conformacional de arilamidas e S-nitrosotióis derivados de SNAP - Sonego, Denise Roberta Neiva [UNIFESP] (2016)
Nitric oxide is a versatile molecule that can be found both in the atmosphere, as in many organisms. Studies have revealed its varied functions, for example, antiplatelet and vasodilatory actions. This study aimed to characterize the nonlinear optical properties of S-nitrosothiols derivatives of SNAP applying the technique known as Z-Scan, which is widely used due its sensitivity and accuracy, and through theoretical calculation to characterize the conformational properties of such molecules, that have more stable conformations syn 1 and syn 2, and are mainly stabilized by intramolecular hydrogen bonds. When DMSO is used as solvent, the molecules dipole moment increases as compared to the gas phase. The compound with greater ability to release nitric oxide was SNO 2-OMe and the one with lower capacity was SNO 2-Br. Unfortunately it was not possible to draw a parallel with the conformation of the molecules and the results of Z-Scan. The thermal diffusivity values are generally higher for the S-nitrosothiols in comparation with the thiols, thermal condutivity showed distinct values for each compound, regardless of the presence of NO and type of substituent.